2007
DOI: 10.1037/0033-2909.133.4.638
|View full text |Cite
|
Sign up to set email alerts
|

Age of acquisition: Its neural and computational mechanisms.

Abstract: The acquisition of new skills over a life span is a remarkable human ability. This ability, however, is constrained by age of acquisition (AoA); that is, the age at which learning occurs significantly affects the outcome. This is most clearly reflected in domains such as language, music, and athletics. This article provides a perspective on the neural and computational mechanisms underlying AoA in language acquisition. The authors show how AoA modulates both monolingual lexical processing and bilingual languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
206
1
10

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(242 citation statements)
references
References 179 publications
25
206
1
10
Order By: Relevance
“…However, as expected, for very low exposure and/or very late AoA, the performance decreases. This is consistent with human language learning, where performance on second-language naming tests tends to be very good, unless the AoA is very late, or exposure to L2 is very limited [11]. As an example, Fig.…”
Section: Modeling Approachsupporting
confidence: 58%
“…However, as expected, for very low exposure and/or very late AoA, the performance decreases. This is consistent with human language learning, where performance on second-language naming tests tends to be very good, unless the AoA is very late, or exposure to L2 is very limited [11]. As an example, Fig.…”
Section: Modeling Approachsupporting
confidence: 58%
“…There has been much discussion of the critical period for learning a second language; as with learning other non-linguistic skills, the learning of an L2 is undeniably affected by the age at which learning begins (Hernandez and Li, 2007). Many alternative hypotheses have emerged concerning these effects in bilingualism (see Hernandez, Li & MacWhinney, 2005;Hernandez & Li, 2007, for an overview). The precise moment that L2 learning begins during development will determine which domains are more sensitive to learning.…”
Section: Introductionmentioning
confidence: 99%
“…The precise moment that L2 learning begins during development will determine which domains are more sensitive to learning. In general, AoA effects are based on developmental constraints, especially the maturation of sensorimotor processing (see 'The sensorimotor hypothesis', Hernandez & Li, 2007). In order to take into account how structural changes evolve across time, we also discuss correlational studies between AoA and L2 proficiency with brain structural measures.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, not only is this true for L2 acquisition but also brain imaging research in neurobiology has revealed a general tendency that early learning (of any type) leads to dedicated neural circuitry that affects the form of cognitive and neural structures at later stages of development (Hernandez and Ping, 2007: p. 646). Moreover, studies have suggested that the attainment of broad native-likeness among late L2 learners is in fact possible (Marinova-Todd, 2003;Hernandez and Ping, 2007;Perani and Abutalebi, 2005). Future research in L2 acquisition must account not only for the typical decline in L2 attainment with age but also for the nativelike achievement levels of which some late learners are capable (Birdsong, 2006: p. 37).…”
Section: Learner-centered Instructionmentioning
confidence: 99%
“…Other factors analyzed include the age of the learner. Researchers have typically aimed at understanding how early versus late learning affects successful acquisition, and discussed this issue in terms of a critical period of acquisition in which language acquisition seemed to depend on appropriate input during this time frame (Hernandez and Ping, 2007). Although critical period effects in L2 learning are still being debated, researchers generally agree that early learning of L2 is associated with higher ultimate proficiency, and age of acquisition is reliably the strongest predictor of ultimate attainment in the language (Birdsong, 2006).…”
Section: Learner-centered Instructionmentioning
confidence: 99%